TOURISM AND COMMUNITY. A STUDY OF COMMUNITY BASED TOURISM IN MANDALA WISATA WANARA WANA UBUD - Puja, Ida Bagus Putu; Aryasih, Putu Ayu (Journal of Business on Hospitality and Tourism, 2020)
Community Based Tourism (CBT) is a tourism activity, a community that is owned and operated, and is managed or coordinated at the community level that contributes to community welfare through sustained livelihood support and protects socio-cultural traditions and resources valuable natural and cultural heritage. The analysis was conducted to analyse the results of interviews with local communities and Monkey Forest’s management regarding the management of tourist attraction based on community. Data is presented in the form of a description to see the community based tourism in managing Monkey Forest. This qualitative study aims to analyze the community in managing tourism attraction of Mandala Wisata Wanara Ubud (Monkey Forest) through community based tourism.